EDUCATION AND PEDAGOGICAL THOUGHTS IN THE WORKS OF IBRAY ALTYNSARIN - Baykabilov Userbai Alimkhanovich (Galaxy International Interdisciplinary Research Journal, 2022)
Ibrai is a genius who has made an invaluable contribution to the development and growth of his people. A great teacher who encouraged his people to study and study art. A teacher who showed how to properly conduct educational work.